Genetics, health and society - Perry, Brea L. (Bingley, U.K. : Emerald, 2015)
Gene-environment interactions and epigenetics are often conceptualized as key mechanisms underlying the influence of social status and social interaction on the distribution of health and illness in society. At the same time, genetic technologies, research, and explanations for health and behavior have rapidly infiltrated popular culture. Genetic information and treatments tailored to individual genomes are often portrayed as a panacea for the future of health care, but have yet to realize their potential, introducing new practical and ethical challenges. This volume focuses on critical issues surrounding the intersection of genetics, health, and society. It provides a critical examination of sociological and biomedical approaches to genomics, including strengths and limitations of each perspective. It also highlights important epistemological and ethical issues which must be confronted before genomics can be leveraged to improve population health. Furthermore, how genetic technologies and testing have been used in medical practice to date is examined, highlighting the costs and benefits of these innovations to society, groups, and individuals.
Heritability studies : methodological flaws, invalidated dogmas, and changing paradigms / Callie H. Burt -- All marked-up in the genetic era : race and ethnicity as "floating signifiers" in genetic and genomic research / Latricia Best, W. Carson Byrd -- Genetic approaches to health disparities / Catherine Bliss -- Making a case for genetics : interdisciplinary visions and practices in the contemporary social sciences / Sara Shostak, Jason Beckfield -- Researching genes, behavior, and society to improve population health : a primer in complex adaptive systems as an integrative approach / Patricia Goodson -- Sociology in an age of genomic instability : copy number variation, somatic mosaicism, and the fallen genome / Martine Lappe<U+0301>, Hannah Landecker -- Natural symptoms? The intersection of social, biological, and genetic determinants of depression in later life / Jason Schnittker -- Frames of reference : marketing the practice and ethics of PGD on fertility clinic websites / Debra Swoboda -- The right to know or not to know : risk notification and genetic counselling / Amaya Gilson ... [et al.] -- Using public-private partnerships to mitigate disparities in access to genetic services : lessons from Wisconsin / Laura Senier, Matthew Kearney, Jason Orne.
Print version record
Keywords: Social Science -- General; Social Science -- Disease & Health Issues; Medical Genetics; Sociology; Medical sociology; Medical genetics; Genetics -- Social aspects; Human genetics -- Social aspects